A urbanização do território e as transformações do campo no município de Macaíba/RN - Santos, Kathiuscia Fernandes dos (2016)
The countryside and the city are increasingly intertwined and among the factors that enable greater intertwining and changes in the relationship between the countryside and the city are communication and transport networks, which, together with other elements, expressing caused territorial changes especially in the field through the territory urbanization process. To discuss this process, we reflect on the rural-urban relationship, commonly, is accomplished through three perspectives: the dichotomous, the continuum and the urbanization of the countryside. However, in our analysis, we propose an urbanization approach from the territorial perspective, which leads us to discuss the urbanization of the territory. This approach permeates the discussion of urban society proposed by Lefebvre (2008, 2001), in which reflections on the new uses of the territory, the new configuration, new forms and content, are needed to understand this process and its current materialization in the territory. Thus, the objective of the research is to understand the planning process of urbanization and the transformation of rural areas in the municipality of Macaíba / RN, from 2000. It should be noted that the choice of this temporality is because it is from 2000 that the rural population is growing again and we started to see the intensification of installing infrastructure in this subspace, which materialized in the territory, imply territorial transformations and changes in both content and form as the rural-urban relationship. To achieve the proposed objective, our research was built as a foundation the dialectical method, because we understand the contradictions between the phenomena, society and space, which are interdependent and whose changes are part of a whole. Thus, we conducted a literature search that could give us the theoretical basis to discuss the key concepts for the development of our work, such as territory, networks, town / country, urban / rural, form / content. Another procedure used was field research, whose study area the rural Macaíba. To represent the universe of our study area we chose three rural communities (The Marias, Stream Blood and Jundiaí), two settlements (Palmares and Eldorado dos Carajás) and two rural districts (Traíras and Cana Brava). The field is critical because during our raids conducted interviews, we apply forms and produce photographic records. In addition, we made visits to organs like EMATER-RN, SEMURB, Department of Agriculture and Department of Health Macaíba where we could collect secondary data and documents. Thus, we pointed out that among the most noticeable changes in the field are the new uses of the territory for: villa with gated communities and housing construction in communities and districts; allocation of areas of industrial interest; installation of research centers and university campuses; and allocation of areas for facilities (schools, health center, parks, public academies of gymnastics), which give a new territorial configuration to the field.